2020
DOI: 10.1089/apc.2020.0004
|View full text |Cite
|
Sign up to set email alerts
|

Integrating HIV Pre-Exposure Prophylaxis into Family Planning Care: A RE-AIM Framework Evaluation

Abstract: We aimed to systematically evaluate the feasibility of integrating HIV prevention services, including preexposure prophylaxis (PrEP), into a family planning setting in a high-prevalence community. We used the RE-AIM Framework (Reach, Efficacy, Adoption, Implementation, Maintenance) to evaluate the integration of HIV prevention services into a family planning clinic over 6 months. Before the integration, PrEP was not offered. We implemented a staff training program on HIV PrEP. We determined the proportion of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…78 One family planning clinic serving predominantly Black women implemented a pilot staff training program to increase PrEP provision, including same-day PrEP, and reported that HIV counseling and PrEP screening increased from 10% at 1 month to >50% at 6 months. 79 Another intervention currently under study trains PrEP clinical change teams at Southern Title X clinics to lead PrEP implementation for women within their family planning services. 80 A complementary strategy to expand PrEP services is to increase the number and type of healthcare professionals who know how to prescribe PrEP.…”
Section: Healthcare System Levelmentioning
confidence: 99%
“…78 One family planning clinic serving predominantly Black women implemented a pilot staff training program to increase PrEP provision, including same-day PrEP, and reported that HIV counseling and PrEP screening increased from 10% at 1 month to >50% at 6 months. 79 Another intervention currently under study trains PrEP clinical change teams at Southern Title X clinics to lead PrEP implementation for women within their family planning services. 80 A complementary strategy to expand PrEP services is to increase the number and type of healthcare professionals who know how to prescribe PrEP.…”
Section: Healthcare System Levelmentioning
confidence: 99%
“…But for some OBGYNs, the ability to add PrEP provision to routine care may seem challenging for OBGYNs that already face challenges with providing multiple components of care with significant time constraints ( 10 ). Frameworks such as RE_AIM (Reach, Efficiency, Adoption, Implementation, Maintenance) have been used to successfully integrate HIV Prevention services despite known barriers like time constraints and insurance barriers ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite some local efforts to promote PrEP implementation in diverse practice settings, most clinicians have not provided PrEP ( 7 , 9 ). Clinicians identified need for education around PrEP provision and some raise concern that addition of counseling and provision of PrEP to already busy clinical environments is challenging ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, our group is working with the LDH to enhance PrEP awareness and uptake among women, following the efforts of other investigators in working with women's health providers and family planning clinics. [20][21][22][23][24] Finally, Louisiana is fortunate to have expanded Medicaid, and thus may have fewer barriers to PrEP access relative to non-Medicaid expansion states. 25 In response to the findings presented in this study, our team is currently investigating the use of Rapid PrEP initiation at the SHC.…”
Section: Discussionmentioning
confidence: 99%